Unbranded - Masters, Ben, 1988- (Book collections on Project MUSE., 2015)
On an epic 3,000-mile journey through the most pristine backcountry of the American West, four friends rode horseback across an almost contiguous stretch of unspoiled public lands, border to border, from Mexico to Canada. For their trail horses, they adopted wild mustangs from the US Bureau of Land Management that were perfectly adapted to the rocky terrain and harsh conditions of desert and mountain travel. A meticulously planned but sometimes unpredictable route brought them face to face with snowpack, downpours, and wildfire; unrelenting heat, raging rivers, and sheer cliffs; jumping cactus.